Exercise hemodynamic evaluation in the management of dasatinib-related pulmonary arterial hypertension: a case report - Shuhei Yamashita; Takahiro Hiraide; Yasuyuki Shiraishi; Yoshinori Katsumata; Masaharu Kataoka; Shogo Fukui; Michiyuki Kawakami; Shinsuke Yuasa; Shinichiro Okamoto; Keiichi Fukuda; Masaki Ieda (Journal of Medical Case Reports)
Abstract Background Dasatinib-related pulmonary arterial hypertension is a rare complication of chronic therapy for hematological malignancies. Pulmonary hypertension often persists despite drug discontinuation and might require vasodilators. Normalizing pulmonary hemodynamics and avoiding the long-term use of vasodilators is challenging. Case presentation Patient was a 55-year-old Japanese man complaining of progressive dyspnea on effort and fatigue. He had a history of hypertension and chronic myeloid leukemia treated with dasatinib. He was diagnosed with dasatinib-related pulmonary arterial hypertension by a right heart catheterization at rest, demonstrating a mean pulmonary artery pressure of 31 mmHg and a normal pulmonary arterial wedge pressure of 6 mmHg. Symptoms and hemodynamics significantly improved after the discontinuation of dasatinib and the initiation of upfront combination therapy of vasodilators. An exercise right heart catheterization, performed more than 2 years after the initiation of vasodilators, showed a mean pulmonary artery pressure of 15 mmHg at rest and 29 mmHg at peak exercise (normal reference value, < 30 mmHg), suggesting normal pulmonary microcirculation. On the basis of these findings, pulmonary vasodilators were discontinued. Notably, a repeat exercise right heart catheterization demonstrated preserved pulmonary microcirculation, and the patient has remained asymptomatic for more than 2 years after discontinuing pulmonary-arterial-hypertension-targeted therapy. Conclusions The evaluation of pulmonary microcirculation by exercise right heart catheterization can be useful for withdrawing pulmonary vasodilators safely in the management of patients with dasatinib-related pulmonary arterial hypertension.